2019
DOI: 10.3390/jcm8050640
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in the Quantification of Biogenic Amines in Biofluids as Biomarkers of Various Disorders: A Review

Abstract: Biogenic amines (BAs) are bioactive endogenous compounds which play a significant physiological role in many cell processes like cell proliferation and differentiation, signal transduction and membrane stability. Likewise, they are important in the regulation of body temperature, the increase/decrease of blood pressure or intake of nutrition, as well as in the synthesis of nucleic acids and proteins, hormones and alkaloids. Additionally, it was confirmed that these compounds can be considered as useful biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 180 publications
(452 reference statements)
0
19
0
Order By: Relevance
“…Two classes of compounds that are likely to be important in the study of aggression are organic acids, which play vital roles in critical metabolic pathways and neurotransmitter turnover (24), and biogenic amines. Neurotransmitters like serotonin, dopamine, norepinephrine, epinephrine, and histamine are all biogenic amines (25).…”
Section: Introductionmentioning
confidence: 99%
“…Two classes of compounds that are likely to be important in the study of aggression are organic acids, which play vital roles in critical metabolic pathways and neurotransmitter turnover (24), and biogenic amines. Neurotransmitters like serotonin, dopamine, norepinephrine, epinephrine, and histamine are all biogenic amines (25).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the previous studies revealed that quenching of QD fluorescence by dopamine may be related to its oxidation to dopamine-quinone by ambient O 2 and therefore an electron-transfer process from QDs to dopamine-quinone species [33,34]. Since the catecholamines show the greatest stability at acidic pH and could be oxidized to a quinone species both in neutral and alkaline conditions, a similar mechanism is likely for both norepinephrine and epinephrine [31]. It is also well-known fact that glutathione reacts easily with quinone compounds, which might make the possible mechanism of interaction between catecholamine NTs and QDs-GSH more complex [35].…”
Section: Excitation-emission Fluorescence Response Patterns Of Gsh Capped Quantum Dotsmentioning
confidence: 99%
“…The diverse influence of neurotransmitters on the fluorescent properties of QDs-GSH is most likely related to the differences in their chemical structure and thus possibly different kind of interactions between NTs and glutathione surface ligands, as well as the core of QDs. At pH 7.4, dopamine (pKa 9.27), norepinephrine (pKa 8.91), epinephrine (pKa 8.85), and serotonin (pKa 9.31) remain in cationic form [31]; GABA is present as zwitterion [10], and acetylcholine has a positive charge on the nitrogen atom; therefore, electrostatic interaction of all investigated NTs with anionic GSH surface ligands may be possible. However, when considering the structure of these chemical compounds, it seems that only amino and hydroxyl functional groups of dopamine, norepinephrine, epinephrine, and serotonin can participate in the formation of hydrogen bonds with GSH [32].…”
Section: Excitation-emission Fluorescence Response Patterns Of Gsh Capped Quantum Dotsmentioning
confidence: 99%
“…Newer microfabrication techniques in particular are advancing, and microchip production using 3D is now under development [ 52 , 53 ]. Overall, CE offers advantages such as reduced sample and reagent consumption, lower operating costs, shorter reaction time, better portability, higher number of theoretical plates, and higher reliability [ 25 , 47 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. Despite many advances in the CE technology, there is still a limited number of medical applications that are routinely performed in a clinical laboratory.…”
Section: Role Of Capillary Electrophoresis In Point-of-care Diagnomentioning
confidence: 99%